2013
DOI: 10.1016/s0325-7541(13)70036-1
|View full text |Cite
|
Sign up to set email alerts
|

Production of anticandidal cotton textiles treated with oak gall extract

Abstract: Candida albicans, one of the most dreadful fungal pathogens threatening humans, could not be easily prevented. The anticandidal activity of oak gall extract, Quercus infectoria (QIE), was investigated as a potential natural alternative to synthetic and chemical fungicides. QIE anticandidal potentiality was confirmed using both qualitative and quantitative assays. Cotton textiles were treated with QIE and then evaluated as anticandidal fabrics. QIE-treated textiles had a potent anticandidal activity, which coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The durability tests, for the treated textiles with plant extracts, indicated that extracts could form strong bonds with textile material (cotton cellulose), so that they preserved most of their antibacterial activity even after two laundering cycles, matching suggestion was introduced from many relevant studies (Ramachand ran et al, 2004;Tayel et al, 2013b) that suggested that antibacterial agents could covalently fixed and interacted onto cotton textiles.…”
Section: Issn: 1687-7497mentioning
confidence: 90%
“…The durability tests, for the treated textiles with plant extracts, indicated that extracts could form strong bonds with textile material (cotton cellulose), so that they preserved most of their antibacterial activity even after two laundering cycles, matching suggestion was introduced from many relevant studies (Ramachand ran et al, 2004;Tayel et al, 2013b) that suggested that antibacterial agents could covalently fixed and interacted onto cotton textiles.…”
Section: Issn: 1687-7497mentioning
confidence: 90%
“…1 × 1 cm 2 cotton fabrics were cut and immersed in extracts solution, at their MBC levels, stirred for 2 h at 50°C, then padded and squeezed using 2 nips and dips to 100% wet pick up. Treated cotton fabric pieces were dried for 3 min at 37°C, as described by Tayel et al (2013). The antimicrobial evaluation of extract-treated fabrics was conducted using ZOI assay on inoculated plates with pathogen.…”
Section: Fabrication Of Extract-treated Cotton Textilesmentioning
confidence: 99%
“…Quercus infectoria tree is located in the Mediterranean region, normally known as oak galls (Greenish 1999;Morales 2021). Q. infectoria extract (QIE) was commended in folkloric remedy for leucorrhea, menstruation, dysentery, hemorrhages, gonorrhea, as well as in mouthwash/gargle being potent antimicrobial and antiviral agent (Tayel et al 2013;Morales 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The textile materials accelerate the growth of bacteria. Some coatings accelerate this process of microorganisms' growth [22]. A study proves that how ordinary fibers like wool and cotton are vulnerable to bacterial growth and the growth of dust fibers hold oxygen, nutrients and water.…”
Section: Introductionmentioning
confidence: 99%